Green roofs: Effects of plant species used on runoff. (2nd August 2018) - Li, XiaoXiao; Cao, JunJun; Xu, PeiXian; Fei, Ling; Dong, Qin; Wang, ZhaoLong
Abstract: Green roofs are becoming a major nature‐based solution worldwide to reduce urban stormwater runoff. Runoff reduction and retention mainly depend on the hydrological characteristics of substrates and the water use strategies of plants. However, little is known about how plant species affect the hydrological performance of green roofs. Two commonly used succulent plants and four turfgrass species were investigated for their impacts on the hydrological performance and runoff reduction of green roof lysimeters under controlled conditions using a rainfall simulator. The results showed that two succulent plants (Sedum lineare and Callisia repens ) did not make significant contributions to canopy interception in any of the four seasons and made only minor contributions to evapotranspiration (ET) water loss in autumn and winter, resulting in minor effects on runoff reduction by the green roofs. Festuca arundinacea contributed 47.4–116.7% of water loss via transpiration and 36.5% of runoff reduction under a 25 mm day −1 rainfall intensity in spring and 48.0% of runoff reduction under a 10 mm day −1 rainfall intensity in winter. Poa pratensis, Lolium perenne, and Agrostis stolonifera also significantly reduced runoff. Runoff reductions by extensive green roofs were mainly caused by ET rather than by their canopy interceptions. Plant shoot biomass and ET were the primary factors controlling the runoff reduction by extensive green roofs. Our results strongly suggest that the runoff reduction capacity of extensive green roofs can be greatly improved by selecting plant species with a higher shoot biomass and ET rate.